(untitled) - Shirai, Shohei (Tokyo, 1970)
This is the whole tale of the most lustrous gems from the sea, the gleaming pearl. The author discusses the history of pearls and their fame as ornaments, the long struggle to perfect the cultured pearl, the way pearls are processed, and, finally, how they are combined with precious metals and stones to create jewels of great beauty and value.
Keywords: Ngọc trai,Pearl fisheries; Nhật Bản,Japan